2020
DOI: 10.1016/j.ecolmodel.2020.109196
|View full text |Cite
|
Sign up to set email alerts
|

Dietary bioaccumulation of persistent organic pollutants in the common sole Solea solea in the context of global change. Part 2: Sensitivity of juvenile growth and contamination to toxicokinetic parameters uncertainty and environmental conditions variability in estuaries

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…A companion paper (Mounier et al, 2020) presents how the model developed here allowed us to better understand the sensitivity of juvenile sole growth and contamination by some POPs to environmental factors affected by Global Changes in estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…A companion paper (Mounier et al, 2020) presents how the model developed here allowed us to better understand the sensitivity of juvenile sole growth and contamination by some POPs to environmental factors affected by Global Changes in estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…These contrasting profiles show that the identification of gender‐specificity in this context must consider the tissue/organ. It has been suggested that fish bioaccumulation is rather due to gender‐specific contaminant elimination (through gametes emission) rather than to differential accumulation (Mounier et al, 2020). Bodiguel et al (2009) used a mechanistic model to study the dynamics of PCB bioaccumulation in the European hake ( Merluccius merluccius ) and observed that female concentrations decreased suddenly during spawning, due to the loss of PCBs (polychlorinated biphenyls) contained in the eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of significant levels of pollutants in sole tissues can affect their physiological performance and harm the health of consumers. Given this, several studies assessing the bioaccumulation capacity and toxicity of different chemical contaminants (organic pollutants and metals) have been conducted using Solea solea as target species (Dierking et al, 2009;Wessel et al, 2010;Trisciani et al, 2011;Cannas et al, 2013;Sanchez-Nogué et al, 2013;Sister et al, 2013;Solé et al, 2013;Cuevas and Zorita, 2018;Mounier et al, 2020aMounier et al, , 2020b, some other study focused on differential mortality in age-0 juveniles (Guinand et al 2011). However, all these studies have focused on the juvenile stage and the ecotoxicity of contaminants at the early life stages of S. solea it is still, up to date, understudied.…”
Section: Changes In Spawning Larval Development and Survival Related ...mentioning
confidence: 99%